The effect of vitamin B1 on heavy menstrual bleeding - Jafari, Azam; Latifian, Ziba; Torkashvand, Roya; Saatchi, Mohammad (Progress in Nutrition, 2019)
Profuse menstrual bleeding is a main reason for a poor quality of life and iron deficiency anemia in women of reproductive age. Therefore, it is necessary to take measures to reduce the volume of such bleeding. Therefore, this study was conducted to determine the effect of vitamin B1 on the volume of menstrual bleeding.  This is a double-blind clinical trial. The study was performed on 98 single students of paramedicine faculty (aged 18-26 years) who suffered from menstrual bleeding volume during 2016-17. The samples were selected provided their bleeding lasted for longer than 7 days and in case more than 14 pads were used by them. Then, 100 mg of vitamin B1 and placebo were administered to the intervention and control groups for 3 months during three consecutive menstrual cycles, respectively. The samples were evaluated for bleeding 1 month before and after intervention (without taking medication or placebo). In this study, Higham’s chart was used to measure bleeding. Data analysis was done using Mann-Whitney test, Wilcoxon rank sum test, and repeated measures test. 83 subjects completed the study. In the intervention group, mean duration of bleeding was decreased from 8.7±1.5 to 5.7±1.21 and from 9.15±1.08 to 8.01±0.78 in intervention and control groups, respectively. The number of pads used in the intervention group decreased from 18.5±3.2 to 11.8±4.2 and from 19.5±2.6 to 18.69±2.23 in control and intervention groups, respectively (P